CARL SCHMITT X HANS KELSEN: DEFENSOR OU SENHOR DA CONSTITUIÇÃO? - Pinto, Roberto Bueno (2015)
The political crises of the contemporary democracies find their explanation in the past arguments composed by detractors of the parliamentarian democratic theory and practice. The debate between Schmitt and Kelsen on the protector of the Constitution and the (il)limitation, which must characterize the exercise of its power, contains one of the juridical and political reasons that exceeds its own time. We suggest that reason still beats and fulfills one of the many grooves of the contemporary democracy’s crisis, i.e., the unfinished debate on the supremacy of law over politics or politics over law, or still, the supremacy of the technique over the world of life (Lebenswelt) or, instead, the world of life over any type of regulation turned to assure the liberties. Starting from that premise this article looks to recognize – aside the self-perception of each author about his theories – who really support a theory composed by a defender, and who by a seignior of the Constitution.